Methods for including information from multi‐arm trials in pairwise meta‐analysis. (25th August 2017) - Rücker, Gerta; Cates, Christopher J.; Schwarzer, Guido
Abstract : Systematic reviewers conducting pairwise meta‐analyses sometimes encounter multi‐arm studies. To include these studies, and to avoid a unit‐of‐analysis error, often two or more arms are combined or the control arm is split. In this tutorial, we present 5 different approaches that can be used. Particularly, we present a novel approach (method 4) that to the best of our knowledge has not been presented before. We demonstrate their application on 3 selected data sets, discuss their scope of application and their advantages and limitations, and give recommendations.